Ethiopia Climate-Smart Agriculture Investments Summary - Tesfaye, Lidya; Barale, Kelsey; Alemayehu, Sintayehu; Nowak, Andreea C.; Jaquet, Stéphanie (Accelerating Impacts of CGIAR Climate Research for Africa, 2023)
In Ethiopia, a group of stakeholders, including representatives from local governments, research institutions, the Ministry of Agriculture, farmers' unions, the private sector, and NGOs, developed the planning framework that formed the basis for Ethiopia's Climate-Smart Agriculture Investment Plan (CSAIP). The CSAIP outlines seven priority investments identified by stakeholders to meet the goals of productivity, adaptation, and mitigation. This Info Note briefly summarizes these prioritized investments, key considerations for success, and the monitoring and evaluation plan.